15th AIAA/CEAS Aeroacoustics Conference (30th AIAA Aeroacoustics Conference) 2009
DOI: 10.2514/6.2009-3168
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Computational and Experimental Techniques for Nacelle Liner Performance Evaluation

Abstract: The Curved Duct Test Rig (CDTR) has been developed to investigate sound propagation through a duct of size comparable to the aft bypass duct of typical aircraft engines. The axial dimension of the bypass duct is often curved and this geometric characteristic is captured in the CDTR. The semiannular bypass duct is simulated by a rectangular test section in which the height corresponds to the circumferential dimension and the width corresponds to the radial dimension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The results obtained in the present study are comparable to those obtained in the previous study 15 . When the liner treatment is symmetric, the difference between the 0-offset and 1D-offset attenuation is small.…”
Section: Left Rightsupporting
confidence: 83%
See 2 more Smart Citations
“…The results obtained in the present study are comparable to those obtained in the previous study 15 . When the liner treatment is symmetric, the difference between the 0-offset and 1D-offset attenuation is small.…”
Section: Left Rightsupporting
confidence: 83%
“…Figure 16 shows the CDTR with the flow path in the 1D-offset curvature. The offset curvature was investigated in a previous paper by the authors 15 with the duct in the 'exhaust' orientation only. It was found that when the treatment is symmetric, the attenuation with 1D-offset is approximately 2 dB greater than the straight duct at all frequencies except at the peak, where the two results are equal.…”
Section: Flow Path Curvature Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial numerical studies and lower TRL tests were used to define the implementation and validate various tools. 7,10,15,18 As confidence in the overall methodology increased, design and testing efforts were pursued in the NASA Glenn Advanced Noise Control Fan (ANCF) Rig, 1921 9- by 15-Foot Low Speed Wind Tunnel, 22,23 and Aeroacoustic Propulsion Laboratory (AAPL). 24 Lessons learned from these projects culminated in the design and flight testing of an advanced inlet liner on the Quiet Technology Demonstrator 3 (QTD3).…”
Section: Application and Assessment Of The Liner Design Methodologymentioning
confidence: 99%